Adsorption of toxic Pb(II) on activated carbon derived from agriculture waste (Mahogany fruit shell): isotherm, kinetic and thermodynamic study. Issue 19 (30th December 2022) - Patil, Suryakant A.; Suryawanshi, Umesh P.; Harale, Namdev S.; Patil, Sandip K.; Vadiyar, Madgonda M.; Luwang, Meitram N.; Anuse, Mansing A.; Kim, Jin H.; Kolekar, Sanjay S.
ABSTRACT: An adsorbent, mahogany fruit shell activated carbon(MFSAC), was derived from environmental friendly raw material, i.e. agriculture waste and explored for bench scale adsorption of toxic Pb(II). A facile MFSAC material was synthesised using a chemical activation method using concentrated sulphuric acid as an impregnating (activating) reagent. So derived adsorbent material was characterised by FTIR, XRD, BET, SEM, EDAX, TGA and XPS techniques to know the properties and plausible adsorption mechanism. Bench scale adsorption of toxic Pb(II) and maximum adsorption capacity of MFSAC were exhibited through batch adsorption experiments. The effect of physico-chemical parameters such as pH (1–7), MFSAC amount (0.5–5.0 g L −1 ), Pb(II) concentration (200–1000 mgL −1 ), contact period (60–600 min) and orbital shaking speed (60–200 rpm) was studied for maximum removal of Pb(II) upto 99.70 ± 0.17%. The experimental data follow the Langmuir adsorption isotherm with a maximum monolayer adsorption capacity 322.28 mg g −1 and pseudo-second-order kinetic uptake rate. The thermodynamic and temperature study revealed that the adsorption process was spontaneous and endothermic in nature (ΔH o  = 43.37 kJ mole −1, ΔS o  = 158.02 J mol −1 K −1 ). Most importantly, the MFSAC adsorbent was successfully regenerated and reused with conspicuous performance up to five consecutive cycles. The bench-scale adsorption with simple synthesis route, good stability and remarkable regeneration capability makes the MFSAC as an encouraging adsorbent for wastewater treatment.